The adjustment mechanism in the euro area - Pietro Biroli; Gilles Mourre; Alessandro Turrini (Intereconomics, 2013)
This paper analyses the adjustment mechanism in the euro area prior to the crisis. Results show that the real exchange rate adjusted to redress cyclical divergences and that after monetary unification, real exchange rate dynamics became less reactive to country-specific shocks but also less persistent. Regulations affecting price and wage nominal flexibility and employment protection play a role in the adjustment mechanism. Indicators of product and labour regulations appear to matter for both the reaction of price competitiveness to cyclical divergences and for the inertia of competitiveness indicators.
Keywords: 330; Kaufkraftparität; Volatilität; Eurozone; Preiswettbewerb; Lohnniveau; Arbeitnehmerschutz; Wirtschaftliche Anpassung; EU-Staaten